Supercritical CO2 Extraction and Characterization of Coriandrum Sativum L. Essential Oil. Issue 2 (7th April 2015) - Dima, Cristian; Ifrim, George Adrian; Coman, Gigi; Alexe, Petru; Dima, Ştefan
Abstract: For the present study, whole coriander seeds harvested in Romania were screened (<4 mm) and minced in order to obtain ground powder with various particle sizes. Three types of ground powder with particle sizes of 500, 630 and 710 μ m were subjected to extraction with supercritical CO2 . The extraction conducted over a period of 210 min was carried out at 150 bar and temperatures of 40 and 50C. The best extraction yield (0.57% w/w) was achieved for the 630‐ μ m particle size ground at 40C; for this temperature, the density of CO2 is higher as well as its solvation power. The chemical composition of the coriander essential oil extracted at maximum yield was determined through gas chromatography; 10 compounds that make up nearly 97% of the extract thus being identified. The antibacterial activity of the coriander essential oil was investigated on three foodborne pathogens: E scherichia coli O157:H7, S almonella spp. and S taphylococcus aureus . The growth of the three pathogens, stored for 10 days at 10C, in the presence of coriander essential oil was proved to be significantly inhibited. Practical Applications: In contrast with the direct use of powdered spices, the addition of spice extracts in food products does not affect their texture. The supercritical CO2 extraction of coriander essential oils is an environmentally friendly technique that results in pure solvent‐free extracts with high biological potential. In addition, the extraction takes place at low temperatures that help prevent the degradation of the biological components. The pure coriander essential oil thus obtained can be processed further (e.g., microencapsulation) to increase its efficiency in food products. The coriander essential oil obtained using the supercritical CO2 extraction has demonstrated an antibacterial activity, which qualifies its use both as condiment and as preservative.